ANALYSIS OF ESG DISCLOSURE LEVELS IN INDONESIAN STATE-OWNED CONSTRUCTION ENTERPRISES: A COMPARISON BEFORE AND AFTER THE IMPLEMENTATION OF POJK 51/2017 - Fia Medana Arieca (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Disclosure of Environmental, Social, and Governance (ESG) has increasingly gained attention in modern business practices, particularly for construction companies that have significant social and environmental impacts. In Indonesia, the issuance of POJK 51/2017 by the Financial Services Authority marked an important milestone in requiring public companies, including state-owned construction enterprises (BUMN Karya), to prepare sustainability reports. This study aims to analyze the comparison of ESG disclosure levels before and after the regulation in four BUMN Karya, namely WIKA, ADHI, PTPP, and WSKT. The methodology employed is content analysis of annual reports and sustainability reports for the 2015–2023 period, using 22 ESG indicators covering environmental, social, and governance aspects. The findings reveal a significant increase after the regulation, where ESG scores that initially averaged 5–7 in the 2015–2017 period surged to more than 19 in 2018–2023, with all companies achieving full scores since 2021. The discussion highlights the crucial role of regulation in driving transparency, with the most substantial improvement observed in the environmental aspect, which had previously been neglected. In conclusion, POJK 51/2017 proved effective in strengthening sustainability practices, although variations remain among companies in terms of the speed of achieving disclosure standards.